Predictors of infection after pulmonary endarterectomy for chronic thrombo-embolic pulmonary hypertension - Maruna, Pavel; Kunstyr, Jan; Plocova, Katerina M; Mlejnsky, Frantisek; Hubacek, Jaroslav; Klein, Andrew A; Lindner, Jaroslav (European journal of cardio-thoracic surgery, 2011)
OBJECTIVE: Pulmonary endarterectomy (PEA) is an effective and potentially curative treatment for chronic thrombo-embolic pulmonary hypertension (CTEPH). The postoperative course after PEA is accompanied by a number of complications, which contribute to the high rate of early postoperative mortality. Markers allowing the early detection of infectious complication during the postoperative period may be of major clinical importance. The aim of the prospective study was to analyse a predictive value of five inflammatory markers to recognise inflammatory complications accompanying PEA before the first clinical signs of infection. METHODS: Eighty-two patients with CTEPH, who underwent PEA using cardiopulmonary bypass (CPB) and deep hypothermic circulatory arrest (DHCA), were included into the study. Procalcitonin (PCT), tumour necrosis factor-α, interleukin (IL)-6, IL-8 and C-reactive protein arterial concentrations were measured before sternotomy and repeatedly up to 72h after the end of surgery. Haemodynamic parameters, infectious and non-infectious complications were recorded. RESULTS: Postoperative course was uncomplicated in 59/82 patients (group 1). Fourteen out of 82 patients (group 2) developed an infection in the first 3 days after surgery (bronchopneumonia, n = 9; bacterial sepsis, n = 5). Nine out of 82 patients (group 3) developed non-infectious complications in the same period. PCT and IL-6 were the only significant independent predictors of infection in days 1-3 after PEA. The area under receiver operating characteristic (ROC) curve calculated for PCT to predict postoperative infection was 0.83 (95% confidence interval (CI): 0.74-0.92) compared with 0.74 (95% CI: 0.68-0.81) for IL-6. With the cut-off 2.3 ng ml(-1), the test characteristics of PCT were as follows: sensitivity, 86%; specificity, 83%; negative predictive value, 92%; and positive predictive value, 84%. CONCLUSIONS: The increase in PCT and IL-6 may allow patients at increased risk of infection after PEA to be identified, allowing earlier institution of antibiotic treatment. These changes that occur before infection can be detected clinically. This finding may make the daily monitoring of PCT post-PEA useful.
Keywords: Pulmonary Embolism; Pulmonary Artery; plicní embolie; Bacterial Infections; C-reaktivní protein; lidé středního věku; Humans; proteinové prekurzory; časná diagnóza; Epidemiologic Methods; ženské pohlaví; Biomarkers; Postoperative Care; Inflammation Mediators; pooperační komplikace; mužské pohlaví; endarterektomie; Middle Aged; Cardiopulmonary Bypass; C-Reactive Protein; biologické markery; Protein Precursors; Interleukin-6; epidemiologické metody; Male; arteria pulmonalis; kalcitonin; mediátory zánětu; plicní hypertenze; senioři; lidé; interleukin-6; kardiopulmonální bypass; Hypertension, Pulmonary; Aged; pooperační péče; Endarterectomy; Postoperative Complications; bakteriální infekce; Early Diagnosis; Female; Calcitonin